Analisis Kualitas Kepuasan Konsumen Terhadap Pelayanan Ack Fried Chicken Mendoyo - Komang Diah Ibnusuari; Pebriansyah Pebriansyah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
ACK Fried Chicken is a fast food restaurant established on April 1, 2015, in Bali, by Mr. I Made Artana (Kompas.Com 12/20/2021). ACK offers a franchise partnership concept for people who want to open a business in the fast food industry, ACK can also help the community in fundraising efforts by exchanging bazaars that apply to all existing ACK outlets. This study aims to analyze and measure the level of consumer satisfaction with the quality of service provided by ACK Fried Chicken Mendoyo. This study uses a quantitative method with a descriptive approach. Data were collected by distributing questionnaires to 30 ACK Fried Chicken Mendoyo consumer respondents as samples. The independent variable (X) in this study is Service Quality, and the dependent variable (Y) is Consumer Satisfaction. Direct research was conducted by researchers on 10/20/2025 at the ACK Mendoyo outlet located on Jln. Denpasar-Gilimanuk, Ds. Pohsanten, Kec. Mendoyo, Kab. Jembrana, Bali. The results of the study showed that the majority of consumers (90%) stated that they were very satisfied, 8% were satisfied, and 2% were quite satisfied with the service of ACK Fried Chicken Mendoyo, indicating that the quality of service provided had met or even exceeded consumer expectations